Tantangan Inklusi Keuangan Syariah Era Disrupsi - Sultoni, Hasan; Santi, Mei; Rifai, Muhammad Saiful (Universitas Muhammadiyah Ponorogo, 2023)
This research aims to know and understand the Disruption Era and its impact on Sharia Financial Inclusion. Financial inclusion is an effort that makes it easy to access a more prosperous life for all people. This research uses a literature review research method, obtaining data from Scientific Journal literature and data related to Islamic Financial Inclusion in Indonesia. This inclusion program is very important for equal access to the entire community, especially for someone who is unbankable. In this program, the role of the government and financial institutions, both conventional and sharia, is very influential. Inclusive, stable finance will be achieved through five pillars and foundations, including; Financial Education Pillar, Community Property Rights Pillar; Product Pillar, Intermediation and Distribution Channels; Financial Services Pillar in the Government Sector; Consumer Protection Pillar. The impact that occurs in the development of Financial Inclusion in the era of disruption is the emergence of FinTech, which is able to open various facilities for consumers in using / utilizing various financial services digitally, such as: payments, loans, investments, and insurance.